SIMULATION EDUCATION AND ITS ROLE IN IMPROVING THE QUALITY OF MEDICAL EDUCATION - Shadmanov, A.K.; Khalmatova , B.T.; Shadmanov , M.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
The article presents the results of the application of simulation educational technologies based on the Tashkent Medical Academy of the Republic of Uzbekistan. The introduction of training simulation courses into the educational process of training medical personnel at all stages of continuous medical education will help reduce medical errors, reduce complications and improve the quality of medical care to the population.